NEW PROSPECTS OF ANTITHROMBOTIC THERAPY IN PATIENTS WITH ATRIAL FIBRILLATIO AND CORONARY ARTERY STENTS: DABIGATRAN POTENTIAL - M. Yu. GILYAROV; E. V. KONSTANTINOVA («REMEDIUM GROUP» Ltd., 2017)
After percutaneous coronary intervention, patients receive double antiplatelet therapy for several months, which includes acetylsalicylic acid and a P2Y12 receptor inhibitor. In most cases, managing the patients with the atrial fibrillation requires adding an anticoagulant drug to the antiplatelet therapy - triple antithrombotic therapy. The rejection of triple therapy in favour of the administration of an anticoagulant and only one antiaggregant is a prospective line of reducing the risk of bleeding in these patients. The number of studies evaluating the effectiveness and safety of such therapy remains limited, and the guidelines for anticoagulant therapy are largely based on the studies of only "stable" patients with atrial fibrillation and on the results of registers, i.e. data of "real-life" clinical practice. The RE-DUAL PCI study showed that the administration of dabigatran in combination with the P2Y12 receptor inhibitor in patients with atrial fibrillation after percutaneous coronary intervention is much safer and no less effective than the classical triple therapy. A special feature of the study was the evaluation of the effectiveness and safety of two doses of dabigatran, each of which was approved for stroke prevention. This provides clinicians with additional options for treating patients with atrial fibrillation after percutaneous coronary intervention.